Risk Factors for Insomnia in Older Adults - Arsa Rama Dani Nugraha; Erikavitri Yulianti; Fidiana Fidiana (Jurnal EduHealth, 2026)
Insomnia is one of the most common sleep disorders experienced by older adults. Its prevalence among this population is relatively high, both nationally and internationally, and it is frequently associated with decreased quality of life, increased risk of chronic diseases, and psychological burden. This article aims to comprehensively review the factors influencing the risk of insomnia in older adults, including lifestyle, psychological conditions, environmental aspects, and physical illnesses. The method employed is a literature review, which involves collecting and analyzing 20 national and international journals published between 2006 and 2024. The findings indicate that insomnia in older adults does not occur in isolation but is influenced by a complex interaction between internal factors (psychological, physical illness, and lifestyle) and external factors (environment). This review is expected to provide both academic and practical contributions, particularly for healthcare practitioners, nurses, and researchers, in formulating evidence-based interventions to improve sleep quality in older adults.